Cookie‐cutter shark Isistius spp. predation upon different tuna species from the south‐western Atlantic Ocean. Issue 4 (21st February 2018) - Niella, Y. V.; Duarte, L. A. G.; Bandeira, V. R.; Crespo, O.; Beare, D.; Hazin, F. H. V.
Abstract : The predation of cookie‐cutter sharks Isistius spp. upon the early life stages of yellowfin tuna Thunnus albacares, skipjack tuna Katsuwonus pelamis and little tunny Euthynnus alletteratus are described. New evidence suggesting a connection between commercial fishing and predation by Isistius sp. is presented, with these sharks biting tunas hooked in surface waters during daylight. The healing patterns of the wounds made by the sharks are described in detail and, although such damage is known to negatively influence market price elsewhere, it is not the case on the south‐east Brazilian coast.